Personality-related determinants of criminal recidivism - Knežević, Goran (Psihologija, 2012)
The goal of this study was to explore personality-related determinants of recidivism, with recidivism being defined as a) the number of lawful sentences a person had (criminal legal recidivism), and b) the number of prison sentences pronounced (penal recidivism). The study was carried out in two independent samples: a) convicts from the Correctional Institution of Belgrade - Penitentiary of Padinska Skela (N=113), and b) convicts from the Special Prison Hospital in Belgrade (N =112). The variables of the Five-Factor Model of Personality (Neuroticism, Extraversion, Openness, Agreeableness and Conscientiousness) were measured, together with two additional basic personality traits: Disintegration (a broad dimension of psychosis-proneness), and Amorality (three factors representing a disposition to amoral forms of behavior). In addition, psychopathy (Manipulative and Antisocial tendencies) - a psychological entity expected to most successfully predict criminal recidivism - was measured as well. The efficiency of prediction of the two criteria of recidivism was assessed separately in each of those two samples. The results revealed differences in the orchestration of predictors depending on the kind of recidivism as the criterion and the severity of offense. The most important predictors of both forms of recidivism in the sample of convicts with lower intensity of criminal behavior were psychopathic traits. However, in the sample of convicts with higher intensity and variety of criminal behavior, the most important predictors of the number of sentences were Antisociality and Amorality Induced by Frustration, while the most important predictors of the number of prison sanctions were Amorality Induced by Brutality and Disintegration